2lnx=ln(6+x)

Simple and best practice solution for 2lnx=ln(6+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2lnx=ln(6+x) equation:


Simplifying
2lnx = ln(6 + x)
2lnx = (6 * ln + x * ln)
2lnx = (6ln + lnx)

Solving
2lnx = 6ln + lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-6ln' to each side of the equation.
-6ln + 2lnx = 6ln + -6ln + lnx

Combine like terms: 6ln + -6ln = 0
-6ln + 2lnx = 0 + lnx
-6ln + 2lnx = lnx

Add '-1lnx' to each side of the equation.
-6ln + 2lnx + -1lnx = lnx + -1lnx

Combine like terms: 2lnx + -1lnx = 1lnx
-6ln + 1lnx = lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
-6ln + 1lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-6 + x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-6 + x)' equal to zero and attempt to solve: Simplifying -6 + x = 0 Solving -6 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + x = 0 + 6 x = 0 + 6 Combine like terms: 0 + 6 = 6 x = 6 Add '-1x' to each side of the equation. x + -1x = 6 + -1x Combine like terms: x + -1x = 0 0 = 6 + -1x Simplifying 0 = 6 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -67.5+x=22.7 | | 6y+18y= | | x+38.6=-82.1 | | 7x+10y=12 | | (a^2b^4)(ab^5)= | | 85x+55x=420 | | 75.5=x+95.2 | | (V-6)(v-2)=0 | | 4C^2-35C+49=0 | | -x+12.8=33.2 | | 9(t-6)+5t=7(2t+5)-8 | | (x-3)(x+7)=o | | 4x(3x+6)=2(x-7) | | 5n^2+7=132 | | 0.1(8)+x=0.4(8+x) | | 16x-100= | | 6y+9=39 | | x+89.6=57.3 | | 3m^2+3=51 | | 86a+43= | | 10y=100x+40fory | | N^2-10=-6 | | 6x-6y=48fory | | 5w+6y=15m | | 34x-6= | | N^2-3=78 | | 64y+28= | | 10x+6(80)=8x+8(80) | | -4x+5=.6 | | 8x+y-11=0 | | 6(x+5)-(6x+30)= | | -7d+3+5(d+2)=7d+3+5d+10 |

Equations solver categories